Narrating the Unspeakable: Order, Mood, and Voice in Indonesia Queer Novel: A Narratological Queer Study - Sahrani, Awahaf (Researchparks Publishing, 2026)
This paper explores the narrative structure of Lelaki Terindah (2004) by Andrei Aksana through the framework of Gérard Genette’s classical narratology—focusing on the elements of order, mood, and voice—while also incorporating postclassical insights from queer perspective. By analyzing how the novel organizes time (order), filters perception (mood), and positions the narrative voice, this study reveals how those narrative forms serve as reflection to the representation of a queer experience in contemporary Indonesia popular literature. Rather than merely identifying structural features, the study interrogates cultural and ideological implications, arguing that the manipulation of narrative time reflect the traumatic experience around homophobia, then mood and also voice reflects the silencing and negotiation of queer identity within a heteronormative society. The novel’s use of shifts in focalization, and narrative distance, and multiple narrative levels, not only structure the story of same-sex love but also mirror the challenges of visibility and repression faced by queer individuals in a context where such identities remain socially marginalized. Through this approach, the paper positions Lelaki Terindah as a site where narrative technique becomes a mode of cultural resistance and personal expression of one’s queerness.